Asking about human papillomavirus vaccination and the usefulness of registry validation: A study of young women recruited using Facebook. Issue 6 (4th February 2015) - Gunasekaran, Bharathy; Jayasinghe, Yasmin; Brotherton, Julia M.L.; Fenner, Yeshe; Moore, Elya E.; Wark, John D.; Fletcher, Ashley; Tabrizi, Sepehr N.; Garland, Suzanne M.
Abstract Background Australia was the first country to implement a government-funded National Human Papillomavirus (HPV) Vaccination Programme. We assessed HPV vaccine uptake comparing self-reported and Register validated estimates, and the knowledge and attitudes of young women with regards to HPV vaccination post-implementation of the programme. Methods Females, aged 16–25 years living in Victoria, Australia, were recruited using targeted advertising on Facebook from May to September 2010, to complete a web-based questionnaire. Results Geographic distribution, Indigenous and socio-economic status of the 278 participants were representative of the target population. Overall, 210/278 (76%) had heard of HPV vaccines, with 162/278 (58%) reporting receipt of at least one dose of vaccine, and 54 (19%) unsure. Verification of HPV vaccination status of 142 consenting participants (51%) showed 71% had received at least one dose. Main reasons for vaccination were for protection against HPV infection and cervical cancer (96%) and because it was free (87%), whereas unvaccinated women were uncertain of their eligibility (50%), concerned about adverse reactions (32%), or perceived that vaccination was not needed if they were monogamous (32%). Conclusion The potential utility of a vaccination register in the context of a national programme is apparent from the large proportion of young women who were unsure of their vaccine status. HPV vaccine knowledge among participants was relatively high suggesting the national programme has successfully communicated to the majority of eligible women, the purpose and limitations of the vaccine. Vigilance is needed to ensure that young women follow through with Pap testing in vaccine eligible cohorts. The ongoing vaccination programme for pre-adolescent girls and boys should communicate to parents that those with one sexual partner can still acquire HPV and that the safety of the vaccine is now well demonstrated.